A masking technique for security in voice band communications - Montesclaros, Porferio S. (1977)
A design philosophy is developed to implement masking of speech signal by pseudo-noise using integrated circuits as circuit building blocks. A method of synchronization is presented. Based on the design philosophy, a low cost experimental model is developed and tested.
Appendix: leaves 76-85.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Masks (Electronics).